PENERAPAN PENDEKATAN THE ACCERELARATED LEARNING DENGAN MENGGUNAKAN TEKNIK MENGAJUKAN PERTANYAAN YANG DITEMPELKAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN ASAM KUMBANG KABUPATEN PESISIR SELATAN - Zulni, Sovia; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2014)
ABSTRAKÂ The aim of this research was to reveal whether the mathematics conceptual understanding of the students taught by using The Accelerated Learning approach with posing questions technique was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of the research was the students in class VIII of MTsN Asam Kumbang registered in academic year 2013/2014. The instrument of the research was an essay posttest on mathematics conceptual understanding whose reliability was 0,79. The result of data analysis indicated that the two sample classes were normally distributed and homogenous. Furthemore, the value of thitung Â and was higer ttabel indicating that the mathematics conceptual understanding of the students taught by using The Accelerated Learning approach with posing questions technique was better than that of students taught by using conventional learning students in class VIII of MTsN Asam Kumbang